The DNA of prophetic speech - Wet, Friedrich W. de (HTS teologiese studies, 2014)
Having to speak words that can potentially abuse the divine connotation of prophetic speech for giving authority to the own manipulative intent poses a daunting challenge to preachers. The metaphorical images triggered by ‘DNA’ and ‘genetic engineering’ are deployed in illustrating the ambivalent position in which a prophetic preacher finds himself or herself; ambivalence between anticipation of regeneration at the deepest level of humanity on the one hand, and disquiet about the possibility of forcing a human being against his or her will into meeting certain prescribed expectations on the other hand. In reflecting on possible responses to this ambivalence, the theological positions of two prolific scholars in the research field of Homiletics, Gijs D.J. Dingemans and Charles L. Campbell, are critically considered from the point of view of the relationship between Christology and Pneumatology. In reflecting on theological markers for a sensible response, the author argues for a pneumatology in which the work of the Spirit consists of grafting the very DNA of our humanity and all its faculties into Christ, the only One who can open up the true life that is intended for humanity by divine grace. It will be in the very genes of a prophet to speak graceful words, because the prophet will have seen the wonder of the working of divine grace in his or her own life and will have embraced it willingly and joyfully.